Pengaruh Pemasangan Energy Saver Pada Beban Rumah Tangga Ditinjau Dari Potensi Penhematan Energi Dan Kualitas Daya - Sukisno, Toto (Semesta Teknika, 2007)
Energy conservation represents one of activity network to identify and evaluate the potency of energy saving an energy system. The effort of energy conservation of electrics in domestic sector which is a lot of conducted by a society is install the energy saver. This appliance is promoted can economize the usage of electrical energy in domestic sector. This paper study the influence of energy saver at domestic load was evaluated from potency of energy saving and power quality. Result of experiment indicate that 1) At resistive load of red hot lamp type, installation of energy saver result the addition consume the real power equal to 2,54% from real power of measurementÂ  to ES 1 and 4,51% to ES 2; 2) At inductive load of type AC, installation of energy saver result the degradation consume the real power equal to 3,72% from real power of measurement to ES 1 and 1,05% to ES 2, while its THD current decrease to become 3,27% for the installation of ES 1 and 3,67% for the installation of ES 2; 3) At non linear load of Personal Computer type, installation of energy saver result the increase of real power consumption equal to 2,07% from real power of measurement and 1,49% to ES 2, while THD current increase to become 3,13% for the installation of ES 1 and its THD current decrease to become 7,84% for the installation of ES 2.